Evaluation of sex hormones and sperm parameters in male epileptic patients. (7th January 2018) - Ocek, L.; Tarhan, H.; Uludağ, F. İ. and Sarıteke, A. and Köse, C. and Colak, A. and Zorlu, F. and Zorlu, Y.
Abstract : Objectives: The aim of this study was to investigate the effect of carbamazepine (CBZ) and sodium valproate (VPA) monotherapy on sexual functions, sex hormones, and semen analysis and quality in male patients with epilepsy. Methods: A total of 59 male patients with epilepsy, of which 30 were on VPA monotherapy and 29 were on CBZ monotherapy, were included in the study between January 2015 and March 2016. A control group was established with 30 healthy males. Luteinizing hormone (LH), follicle‐stimulating hormone (FSH), prolactin (PRL), free testosterone (fT), estradiol (E2), sex hormone‐binding globulin (SHBG) levels and bioactive testosterone (BAT)/bioactive estradiol (BAE), and BAT/LH ratio were studied in groups. All groups received semen analysis and International Index of Erectile Function Scale (IIEF‐5) test for erectile dysfunction. Results: E2 and DHEAS levels were higher in VPA and CBZ groups compared to control group ( P < .001, P = .014). The decrease in fT levels in the VPA group was statistically significant ( P = .038). No significant difference was detected in levels of SHBG, LH, and FSH ( P > .05). BAT/BAE ratios were low both in VPA and CBZ groups ( P < .001; P < .001), while BAT/LH ratios were low only in CBZ group ( P = .033). In semen analysis, semen volume and number of normal sperms were found to be significantly lower in patients receiving antiepileptic drugs compared to control group ( P < .05). There were no differences between the groups in rates of abnormal sperm morphology. IIEF‐5 scores were found to be significantly lower in VPA and CBZ groups ( P < .001). Conclusion: VPA or CBZ therapy may lead to dysregulation of sex hormones, sexual dysfunction, and alterations in semen analysis in male patients with epilepsy. This must be considered for the selection of antiepileptic drugs in young male patients.